SIMBOL MASKULINITAS DALAM ORNAMEN BUDAYA BUGIS DI FILM TARUNG SARUNG: ANTARA TRADISI DAN MODERNITAS: SYMBOLS OF MASCULINITY IN BUGIS CULTURAL ORNAMENTS IN THE FILM TARUNG SARUNG: BETWEEN TRADITION AND MODERNITY - Ahmad Auliya Zul Hazmi; Acep Iwan Saidi (Jurnal Dimensi Seni Rupa dan Desain, 2024)
The film Tarung Sarung is a cinematic work that highlights the richness of Bugis culture in Makassar, Indonesia. This film depicts the masculinity of Bugis men through characters and settings that highlight the attributes of courage, strength and honor. The main character in this film is depicted as an ordinary young man from the city who develops over the course of the story into a warrior skilled in martial arts. This research aims to analyze the symbols of masculinity in Bugis cultural ornaments in the film Tarung Sarung and find out the meaning of the symbols of masculinity represented. This research uses a descriptive qualitative approach with Charles Sanders Peirce's semiotic analysis method. This research identifies and analyzes the meaning of symbols of masculinity represented in Bugis cultural ornaments in the film Tarung Sarung. The research results show that the symbols of masculinity in the film Tarung Sarung are closely related to the cultural and social values that are highly upheld by the Bugis community. These symbols emphasize the role of men in various aspects of life, from the family to the wider community. Strength, resilience, leadership, authority, wisdom, and discipline are central themes in this representation, showing that masculinity in Bugis culture is closely related to the ability to protect, defend, lead, and maintain cultural values. This research provides several suggestions for developing further studies by exploring the representation of symbols of masculinity in other cultures, combining various analytical methods for a more comprehensive understanding, and examining audience acceptance of representations of masculinity in films.